Supplementation of Pumpkin Seed Oil and SCFASs as a Prospective Biotherapeutic to Preserve Gut Natural Microbiota of Colitis Mice - Putu Oky Ari Tania; Dorta Simamora; Jimmy Hadi Widjaja; Rini Purbowati (The Indonesian Journal of Infectious Diseases, 2025)
Background: Ulcerative Colitis (UC) is an inflammatory disease in the colon, due to the disruption of the interaction between the immune response and the intestinal microbiota in a genetically susceptible host. The imbalance between commensal and pathogenic intestinal microbiota promotes inflammation. This study aims to explore the efficacy of pumpkin seed oil and SCFAs in maintaining the intestinal microbiota in UC model mice. Methods: Four groups, K1, K2, K3, and K4, as health control given distilled water (K1); K2, K3, and K4 induced UC with 2% DSS, followed by administration of Short Chain Fatty Acids (SCFAs) (K3), supplementation of SCFAs and pumpkin seed oil (K4). The number of colonies measured microbiota diversity (log CFU/mL/g) in NA, EMB, MRSA, and McConkey media. Hemoglobin and hematocrit were also measured to assess anemia. Results: The average number of bacterial colonies that grew on NA, EMB, MRSA, and McConkey media in K4 was 7.65, 5.78, 7.85, and 6.20, respectively, and the average HB and hematocrit levels were 14.2 g/dL and 42%, respectively. There was greater microbiota diversity and lactobacillus bacteria in UC rats given pumpkin seed oil and SCFAs, with fewer Enterobacteriaceae and E. coli than in the UC model. The increase in HB and hematocrit levels also showed the same trend. Conclusion: Pumpkin seed oil at a dose of 100 mg/kg and SCFAs can be a prospective biotherapy for maintaining the balance of the natural microbiota and increasing HB levels.